PENGARUH DEBT TO EQUITY RATIO, RASIO PASAR DAN TOTAL ASSETS TURN OVER TERHADAP RETURN SAHAM PADA PERUSAHAAN PROPERTY YANG TERDAFTAR DI ISSI - Noni Ayunda Sari; Sri Rahayu; Zufrizal .; Lusi Elviani Rangkuti (Universitas Islam Islam Sumatera Utara, 2021)
This study aims to see how much Debt To Equity Ratio (DER), Market Ratio (Price Book Value) and Total Asset Turn Over (TATO) Influence On Property Companies Listed in ISSI. The number of samples in this study as many as 10 samples of the company and research conducted from 2016-2018. The data analysis methods used to test hypotheses are descriptive analysis test, classic Assumption Test, Multiple linear analysis test, and Hypothesis Test which is processed in a statistical manner and using Statistic for product and service solution (SPSS) program version 25.00 year 2020. The results showed that variable Debt To equity Ratio (DER), Market Ratio (Price book value) and Total Asset Turn Over (TATO) simultaneously have a significant influence on Stock Return. While partially the effect varies, Debt To Equity Ratio and Total Asset Turn Over have no significant effect on Stock Return. While the market ratio (Price Book value) has a significant influence and has a negative direction towards Stock Return.